Clinical case of progressive pulmonary mycobacteriosis with potential genetic predisposition in a patient with mild bronchial asthma - Natalia N. Makariantz; Maria A. Karnaushkina; Svetlana A. Salamaikina; Konstantin O. Mironov; Sergey L. Babak; Anastasia D. Strutynskaya (LLC "MEDIAFORMAT", 2024)
Mycobacteriosis is an infectious disease caused by opportunistic non-tuberculous microbacteria in patients with chronic respiratory pathology and decreased immunological reactivity. The number of patients with this pathology is increasing not only in Russia, but throughout the world. Scientists' attention was drawn to the fact that the isolation of non-tuberculous mycobacteria from patient's sputum samples does not correlate with the incidence of non-tuberculous mycobacteriosis and the need for its treatment. This may be due to the presence of gene polymorphisms that affect the structure and functional characteristics of innate immune factors. The article presents a rare clinical case of non-tuberculous mycobacteriosis caused by Mycobacterium avium in a 50-year-old woman without severe concomitant diseases and secondary immunodeficiency. The genetic study revealed polymorphic gene alleles, which may predispose this patient for the infection and severe course of this disease.